Timing of sentinel node biopsy independently predicts disease-free and overall survival in clinical stage I-II melanoma patients: A multicentre study of the Italian Melanoma Intergroup (IMI). (September 2020) - Mandalà, Mario; Galli, Francesca; Patuzzo, Roberto; Maurichi, Andrea; Mocellin, Simone; Rossi, Carlo R.; Rulli, Eliana; Montesco, Maria; Quaglino, Pietro; Caliendo, Virginia; De Giorgi, Vincenzo; Merelli, Barbara; et al.
Abstract: Background: Sentinel lymph node biopsy (SNB) still remains a key procedure to appropriately stage melanoma patients and to select those who are candidate to novel treatments with immunotherapy and targeted therapy in the adjuvant setting. The impact of timing of SNB on disease-free survival (DFS) and overall survival (OS) is still unclear. Material and methods: The study was conducted at 6 Italian Melanoma Intergroup (IMI) centres and included 8953 consecutive clinical stage I-II melanoma patients who were diagnosed, treated, and followed up between November 1997 and March 2018. All patients were prospectively included in dedicated IMI database. Multivariable Cox regression analyses were performed to investigate how baseline characteristics and time interval until SNB are related to DFS and OS. Results: Considering the whole population, at multivariable analysis, after adjusting for age, gender, Breslow thickness, site, ulceration, and the SNB status, a delay in the timing of SNB was associated with a better DFS (adjusted hazard ratio [aHR, delayed versus early SNB] 0.98, 95% confidence interval [CI] 0.97–0.99, p < 0.001) and OS (aHR 0.98, 95% CI 0.97–0.99, p = 0.001). Specifically, in patients with a negative SNB status, a beneficial impact of delayed SNB (i.e. at least 32 days after primary excision) was confirmed for DFS (aHR 0.70, 95%CI 0.63–0.79, p < 0.001) and OS (aHR 0.69, 95%CI 0.61–0.78, p < 0.001), whereas in those with a positive SNB status, DFS (aHR 0.96, 95%CI 0.84–1.09, p = 0.534) and OS (aHR 0.94 95%CI 0.81–1.08, p = 0.374) were not significantly different in patients with early or delayed SNB. Conclusions: Our study does not support a strict time interval for SNB. These results may be useful for national guidelines, for counselling patients and reducing the number of high urgency referrals. Highlights: Sentinel lymph node biopsy (SNB) is a key procedure to stage melanoma patients (MPs). In our series, the time interval of SNB is irrelevant in MPs with positive sentinel lymph node. A delayed SNB biopsy is not detrimental in clinically stage I-II MPs.